A simple approach to overcome the problems arising from the Keynesian stability condition - Reiner Franke (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2017)
The Keynesian stability condition is a necessary assumption for the IS equilibrium concept to make economic sense. With reasonable values for the saving parameter(s), however, it typically implies excessively strong multiplier effects. This is more than a cosmetic issue, not least because any simulation study of an otherwise ambitious model will thus be fraught with severe problems along some of its dimensions. The present paper demonstrates that by introducing proportional tax rates on production, corporate income and personal income, the multipliers will be considerably dampened. Within an elementary Kaleckian framework, it also advances a fairly satisfactory numerical calibration.
Keywords: C02; D84; E12; E30; 330; investment multiplier; proportional taxes; public debt; functional finance; moment matching